Natural Killer Cell Activation Receptor NKp30 Oligomerization Depends on Its N-Glycosylation - Skořepa, Ondřej; Pazicky, Samuel; Kalousková, Barbora; Bláha, Jan; Abreu, Celeste; Ječmen, Tomáš; Rosůlek, Michal; Fish, Alexander; Sedivy, Arthur; Harlos, Karl; Dohnálek, Jan; Skálová, Tereza; et al. (Cancers, 2020)
NKp30 is one of the main human natural killer (NK) cell activating receptors used in directed immunotherapy. The oligomerization of the NKp30 ligand binding domain depends on the length of the C-terminal stalk region, but our structural knowledge of NKp30 oligomerization and its role in signal transduction remains limited. Moreover, ligand binding of NKp30 is affected by the presence and type of N-glycosylation. In this study, we assessed whether NKp30 oligomerization depends on its N-glycosylation. Our results show that NKp30 forms oligomers when expressed in HEK293S GnTI- cell lines with simple N-glycans. However, NKp30 was detected only as monomers after enzymatic deglycosylation. Furthermore, we characterized the interaction between NKp30 and its best-studied cognate ligand, B7-H6, with respect to glycosylation and oligomerization, and we solved the crystal structure of this complex with glycosylated NKp30, revealing a new glycosylation-induced mode of NKp30 dimerization. Overall, this study provides new insights into the structural basis of NKp30 oligomerization and explains how the stalk region and glycosylation of NKp30 affect its ligand affinity. This furthers our understanding of the molecular mechanisms involved in NK cell activation, which is crucial for the successful design of novel NK cell-based targeted immunotherapeutics.
Keywords: NK cell; NKp30; glycosylation; B7-H6; oligomerization